Mobilisation of critically ill patients receiving norepinephrine: a retrospective cohort study - Maximilian Lindholz; Clara M. Schellenberg; Julius J. Grunow; Simone Kagerbauer; Annette Milnik; Daniel Zickler; Stefan Angermair; Anett Reißhauer; Martin Witzenrath; Mario Menk; Sebastian Boie; Felix Balzer; et al. (figshare, 2022)
Abstract Background Mobilisation and exercise intervention in general are safe and feasible in critically ill patients. For patients requiring catecholamines, however, doses of norepinephrine safe for mobilisation in the intensive care unit (ICU) are not defined. This study aimed to describe mobilisation practice in our hospital and identify doses of norepinephrine that allowed a safe mobilisation. Methods We conducted a retrospective single-centre cohort study of 16 ICUs at a university hospital in Germany with patients admitted between March 2018 and November 2021. Data were collected from our patient data management system. We analysed the effect of norepinephrine on level (ICU Mobility Scale) and frequency (units per day) of mobilisation, early mobilisation (within 72 h of ICU admission), mortality, and rate of adverse events. Data were extracted from free-text mobilisation entries using supervised machine learning (support vector machine). Statistical analyses were done using (generalised) linear (mixed-effect) models, as well as chi-square tests and ANOVAs. Results A total of 12,462 patients were analysed in this study. They received a total of 59,415 mobilisation units. Of these patients, 842 (6.8%) received mobilisation under continuous norepinephrine administration. Norepinephrine administration was negatively associated with the frequency of mobilisation (adjusted difference -0.07 mobilisations per day; 95% CI − 0.09, − 0.05; p ≤ 0.001) and early mobilisation (adjusted OR 0.83; 95% CI 0.76, 0.90; p ≤ 0.001), while a higher norepinephrine dose corresponded to a lower chance to be mobilised out-of-bed (adjusted OR 0.01; 95% CI 0.00, 0.04; p ≤ 0.001). Mobilisation with norepinephrine did not significantly affect mortality (p > 0.1). Higher compared to lower doses of norepinephrine did not lead to a significant increase in adverse events in our practice (p > 0.1). We identified that mobilisation was safe with up to 0.20 µg/kg/min norepinephrine for out-of-bed (IMS ≥ 2) and 0.33 µg/kg/min for in-bed (IMS 0–1) mobilisation. Conclusions Mobilisation with norepinephrine can be done safely when considering the status of the patient and safety guidelines. We demonstrated that safe mobilisation was possible with norepinephrine doses up to 0.20 µg/kg/min for out-of-bed (IMS ≥ 2) and 0.33 µg/kg/min for in-bed (IMS 0–1) mobilisation.
Keywords: Medicine; Cell Biology; Sociology; 59999 Environmental Sciences not elsewhere classified; 69999 Biological Sciences not elsewhere classified; Science Policy